2019
DOI: 10.1155/2019/1582590
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastric and Small-Intestinal Mucosal Injury in Elderly Patients Taking Enteric-Coated Aspirin by Magnetically Controlled Capsule Endoscopy

Abstract: Objective To investigate aspirin-related gastric and small-intestinal mucosal injury in elderly patients by magnetically controlled capsule endoscopy (MCCE). Methods Patients taking enteric-coated aspirin attending the outpatient department of Beijing Anzhen Hospital, Capital Medical University, from September 2017 to July 2019 underwent MCCE to assess injury to the gastric and small-intestinal mucosa. The patients were divided into the elderly group (age ≥ 60 years) and middle-aged group (45 years ≤ age < 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
10
0
2
Order By: Relevance
“… 20 , 21 Additionally, the degree of this small bowel mucosal injury was greater in elderly patients taking ECA than middle-aged patients. 10 In another case control study, the risk of upper GI complications was similar for both ECA and non-ECA. So, the authors concluded that the coating did not adjust the effect of aspirin.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 20 , 21 Additionally, the degree of this small bowel mucosal injury was greater in elderly patients taking ECA than middle-aged patients. 10 In another case control study, the risk of upper GI complications was similar for both ECA and non-ECA. So, the authors concluded that the coating did not adjust the effect of aspirin.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanisms by which aspirin causes GI mucosal damage are thought to be by both direct topical injury on the epithelium and mainly, a systemic effect associated to prostaglandin depletion. 9 , 10 Different research has mentioned the risk factors for aspirin-induced GI complications, such as higher aspirin dose, advanced age, history of peptic ulcer disease, use of combinations of non-steroidal anti-inflammatory drugs and concomitant use of drugs such as steroids or anticoagulants. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…The preliminary results show that MCCG is of considerable benefit to the elderly and is generally safe. Another study by Gao et al [40] shows that MCCG can monitor aspirin-related gastric mucosal lesions in elderly patients and guide treatment decisions. In 2018, a clinical study in Ruijin Hospital Affiliated to Shanghai Jiaotong University recruited 84 minor patients hospitalized in the pediatric department who underwent MCCG examinations, with an average age of 12 ± 3:2 years.…”
Section: Robotic-type Mccementioning
confidence: 99%
“…развитию ЖКК всегда предшествует повреждение слизистой оболочки ЖКТ. При помощи капсульной эндоскопии было установлено, что повреждающее воздействие антитромботических препаратов не ограничивается слизистой верхнего отдела ЖКТ, а распространяется также и на нижний от-дел, затрагивая тонкий и толстый кишечник [182,[185][186][187]. В последние годы наблюдается тенденция к снижению частоты ЖКК из верхнего отдела ЖКТ и, соответственно, увеличению -из нижнего отдела ЖКТ, связанная отчасти с более высокой распространённостью дивертикулов толстого кишечника и ангиодисплазии в пожилом возрасте.…”
Section: возможности гастро-и энтеропротекции у пожилых пациентов получающих антитромботическую терапиюunclassified